Corrosion of the metal parts of diesel engines in biodiesel-based fuels - Nguyen, Xuan Phuong; Vu, Hai Nam (International Journal of Renewable Energy Development, 2019)
Biodiesel, an environmentally-friendly bio-fuel, has been regarded as one of the most promising alternatives to fossil fuels whose use is rampant in the transportation sector. However, it is important that the corrosive effects of this fuel on engines are studied. This work reviews the corrosiveness that biodiesel exerts on various engine components, especially those made out of metals. First, an analysis of the corrosion mechanisms of metals exposed to biodiesel is provided. The conventional and advanced analysis methods will be applied to measure the level of corrosiveness in static immersion test, and to assess the formation of secondary products, if any, in biodiesel and any metal strips in contact with biodiesel-based fuel. The use of inhibitions to guard against corrosion will be mentioned. Lastly, several significant causes of metal corrosion, namely, the presence of dissolved oxygen and oxidation products, TAN change, a rise in dissolved water, the presence of metals, and the changes in biodiesel properties will also be presented. Â©2019. CBIORE-IJRED. All rights reserved